2011
DOI: 10.1111/j.1439-0272.2010.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA sperm damage correlates with nuclear ultrastructural sperm defects in teratozoospermic men

Abstract: Sperm morphology has consistently been the best indicator of male fertility. Transmission electron microscopy currently provides the most information on the subcellular details of sperm structure. Recently, assessment of sperm DNA damage has been employed to assess fertility potential. The purpose of this work was to link sperm DNA damage, evaluated by an intercalated fluorescent dye, with the structural characteristics of sperm. Conventional semen analysis was performed on samples from men undergoing fertilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…On the other hand, the ultrastructural morphology of sperm of O. niloticus collected from LM displays some alternations including nuclear distortion changes in head morphology, incomplete chromatin condensation, and shortage of bilateral fins of the flagellum, wavy and ruptured plasma membrane. As well as, the presence of some vacuoles and the relative decreases in the density of chromatin condensation might be associated with chromosomal abnormalities, which is associated with decrease fertility potential [46,47]. Moreover, LM fish's spermatozoa revealed the presence of few numbers and large sized mitochondria in front of the proximal centriole toward the lateral aspects of the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the ultrastructural morphology of sperm of O. niloticus collected from LM displays some alternations including nuclear distortion changes in head morphology, incomplete chromatin condensation, and shortage of bilateral fins of the flagellum, wavy and ruptured plasma membrane. As well as, the presence of some vacuoles and the relative decreases in the density of chromatin condensation might be associated with chromosomal abnormalities, which is associated with decrease fertility potential [46,47]. Moreover, LM fish's spermatozoa revealed the presence of few numbers and large sized mitochondria in front of the proximal centriole toward the lateral aspects of the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms proposed to resolve the etiology of DNA damage include apoptosis, oxidative stress, and abnormal chromatin packaging [Ménézo et al 2010;Miller et al 2010]. Many studies have indicated that there is a positive relationship between sperm DNA fragmentation and large nuclear vacuoles in the sperm nuclear area [Oliveira et al 2010a;Skowronek et al 2012;Sakkas and Alvarez 2010]. Furthermore, several studies reported that large vacuoles were linked with chromatin condensation failure [Gopalkrishnan et al 2000;Perdrix et al 2011;Boitrelle et al 2011;Franco et al 2012;Cassuto et al 2012].…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructure of sperm head, neck and tail can be analyzed and quantified by scanning or transmission electron microscopy (Moretti et al 2007, Collodel et al 2009a,b, Skowronek et al 2010, Visco et al 2010, Skowronek et al 2012, Collodel et al 2013, Gatimel et al 2013.…”
Section: Evaluation Of Sperm Morphologymentioning
confidence: 99%